A prebaked anode for aluminum and its composition
By adjusting the formula of pre-baked anode composition for aluminum and adding residual electrode materials for large particles, the balance between pressure strength and apparent density and resistivity in the production of high sulfur petroleum coke is solved, and the effect of increasing pressure strength and reducing resistivity is achieved, which is suitable for the high current efficiency needs of aluminum electrolytic companies.
Patent Information
- Application Number
- CN202410929058.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-11
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-07-11
AI Technical Summary
When using high-sulfur petroleum coke to produce pre-baked anodes for aluminum, it is difficult to maintain or increase the apparent density and reduce the resistivity while increasing the pressure strength, which cannot meet the requirements of aluminum electrolytic companies for high current efficiency.
By adjusting the composition formula of the prebaked anode for aluminum, the residual electrode containing large particles is increased, and the partial coarse, medium and fine coke are replaced, and the specific surface area of the composition particles is reduced, thereby improving the pressure resistance strength while maintaining or increasing the apparent density and reducing resistivity.
It achieves the improvement of the pressure resistance strength of the pre-baked anode for aluminum without reducing the apparent density and resistivity, and improves the resistance to strong current shock, which is suitable for improving current strength and reducing the demand for consumables.
Smart Images

Figure GDA0005195826380000051 
Figure GDA0005195826380000052 
Figure GDA0005195826380000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrode materials, and in particular relates to a prebaked anode using high-sulfur coke as a raw material and a composition thereof. Background Art
[0002] Aluminum prebaked anode is the electrode material for aluminum electrolysis. It is responsible for conducting electricity and participating in electrochemical reactions. It is called the "heart" of the electrolytic cell. Its quality has a direct impact on electrolytic production. The non-ferrous metal industry standard YS / T 285-2012 recommends its apparent density, true density, compressive strength, flexural strength, room temperature resistivity and other indicators. In order to improve the current efficiency, some aluminum electrolysis enterprises have increased the anode current density to 0.82A / cm 2 The above puts higher requirements on the resistivity and compressive strength of prebaked anodes for aluminum.
[0003] With the development of the negative electrode material industry, better quality low-sulfur and low-impurity petroleum coke has been increasingly used in the production of negative electrode materials. However, in order to reduce production costs, prebaked anodes for aluminum can only be produced using a large amount of high-sulfur petroleum coke. The high-sulfur petroleum coke has a low stacking density after calcination, which results in reduced volume density and compressive strength of prebaked anodes for aluminum.
[0004] Therefore, it is an urgent problem for carbon plants to produce prebaked anodes with high compressive strength suitable for aluminum electrolysis using high-sulfur petroleum coke as the main raw material. In view of this, the present invention proposes a new prebaked anode and its composition, which can produce prebaked anodes with high compressive strength using high-sulfur coke as the raw material. Summary of the invention
[0005] The object of the present invention is to provide a composition for a prebaked anode for aluminum. The prebaked anode for aluminum prepared by the composition increases the compressive strength of the prebaked anode for aluminum without reducing the apparent density or increasing the resistivity.
[0006] In order to achieve the above purpose, the technical solution adopted is:
[0007] A composition of a prebaked anode for aluminum, comprising: coarse coke, medium coke, fine coke, residual anode material and powdered coke;
[0008] The coarse coke has a particle size of 3-6 mm accounting for more than 90wt%;
[0009] The proportion of the particles with a particle size of 1-3 mm in the middle coke is greater than 85wt%;
[0010] The fine coke has a particle size of 0.075-1 mm accounting for more than 90wt%;
[0011] The powdered coke has a particle size of less than 0.075 mm accounting for 60±5wt%;
[0012] The residual electrode material having a particle size of 6-12 mm accounts for no less than 35wt%.
[0013] Furthermore, the residual electrode material includes: coarse coke, medium coke, fine powder coke and large particle material.
[0014] The particle size of the large particles is 6-12 mm;
[0015] The coarse coke particle size is 3-6 mm;
[0016] The particle size of the middle coke is 1-3 mm;
[0017] The particle size of the fine coke powder is 0-1 mm.
[0018] Furthermore, the content of large particles in the composition is not less than 5wt%.
[0019] Furthermore, the contents of the components in the residual electrode material are as follows: large particle material ≥ 35wt%, coarse coke 25-30wt%, medium coke 15-25wt%, and fine powder coke less than 25wt%.
[0020] Furthermore, the contents of the components in the composition are: coarse coke 18-20wt%, medium coke 25-27wt%, fine coke 7-10wt%, residual electrode material 15-18wt%, and powder coke 32-34wt%.
[0021] Another object of the present invention is to provide a prebaked anode for aluminum, which is prepared using the above-mentioned composition and has the advantages of high compressive strength, good apparent density and low resistivity.
[0022] In order to achieve the above purpose, the technical solution adopted is:
[0023] A prebaked anode for aluminum is prepared by using the above composition.
[0024] Furthermore, the prebaked anode has a compressive strength greater than 40 MPa, a resistivity less than 60 μΩ·m, and a volume density greater than 1.55 g / cm 3 .
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The prebaked anode for aluminum and the composition thereof described in the present invention improve the compressive strength of the prebaked anode for aluminum by adjusting the formula and adding residual electrode materials containing large particles, thereby improving the impact resistance of the prebaked anode for aluminum to strong currents, so that aluminum electrolysis can increase the current intensity, increase production and reduce consumption, and have the basis of electrode materials without reducing the apparent density or increasing the resistivity.
[0027] 2. The prebaked anode for aluminum and its composition described in the present invention reduces the consumption of asphalt (0.2-0.5%) by adding residual electrode material containing large particles to replace part of the coarse, medium and fine coke in the original formula, thereby reducing the specific surface area of the particles of the composition.
[0028] 3. The prebaked anode for aluminum and the composition thereof described in the present invention are simple in method, easy to implement and suitable for industrial production. DETAILED DESCRIPTION
[0029] In order to further illustrate the prebaked anode for aluminum and its composition of the present invention and achieve the intended purpose of the invention, the following is a detailed description of the specific implementation, structure, features and efficacy of the prebaked anode for aluminum and its composition according to the present invention in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0030] The following will further introduce the aluminum prebaked anode and its composition in detail in conjunction with specific embodiments:
[0031] According to the existing formula theory of prebaked anodes for aluminum, increasing the proportion of large-particle formula appropriately will help improve the compressive strength of prebaked anodes for aluminum. However, with the increase of large-particle materials, its resistivity increases and its apparent density decreases, and its appearance deteriorates. The existing technology must form a balance between the proportion of large-particle materials and the resistivity and apparent density. However, the existing technology increases the proportion of large-particle materials in calcined coke, which can appropriately improve the compressive strength of the anode, but its powder resistivity increases and its apparent density decreases, which cannot meet the requirements of electrolytic aluminum enterprises to strengthen current. When using high-sulfur petroleum coke to calcine calcined coke for production, it is difficult to achieve a balance between apparent density, resistivity and compressive strength under the current conventional formula.
[0032] In order to solve the above technical problems, the present invention proposes a prebaked anode for aluminum and its composition, which achieves the purpose of increasing the compressive strength of the prebaked anode for aluminum without reducing the apparent density and increasing the resistivity by improving the existing formula. The technical solution of the present invention is:
[0033] A composition of a prebaked anode for aluminum, comprising: coarse coke, medium coke, fine coke, residual anode material and powdered coke;
[0034] The coarse coke has a particle size of 3-6 mm accounting for more than 90wt%;
[0035] The proportion of the particles with a particle size of 1-3 mm in the middle coke is greater than 85wt%;
[0036] The fine coke has a particle size of 0.075-1 mm accounting for more than 90wt%;
[0037] The powdered coke has a particle size of less than 0.075 mm accounting for 60±5wt%;
[0038] The residual electrode material having a particle size of 6-12 mm accounts for no less than 35wt%.
[0039] Preferably, the residual electrode material includes: coarse coke, medium coke, fine powder coke and large particle material.
[0040] The particle size of the large particles is 6-12 mm;
[0041] The coarse coke particle size is 3-6 mm;
[0042] The particle size of the middle coke is 1-3 mm;
[0043] The particle size of the fine coke powder is 0-1 mm.
[0044] Further preferably, the content of large particles in the composition is not less than 5 wt %.
[0045] Further preferably, the contents of the components in the residual electrode material are as follows: large particle material ≥ 35wt%, coarse coke 25-30wt%, medium coke 15-25wt%, and fine powder coke less than 25wt%.
[0046] Preferably, the contents of the components in the composition are: coarse coke 18-20wt%, medium coke 25-27wt%, fine coke 7-10wt%, residual electrode material 15-18wt%, and powder coke 32-34wt%.
[0047] Another object of the present invention is to provide a prebaked anode for aluminum, which is prepared using the above-mentioned composition and has the advantages of extremely high compressive strength, good apparent density and low resistivity.
[0048] In order to achieve the above purpose, the technical solution adopted is:
[0049] A prebaked anode for aluminum is prepared by using the above composition.
[0050] Preferably, the prebaked anode has a compressive strength greater than 40 MPa, a resistivity less than 60 μΩ·m, and a bulk density greater than 1.55 g / cm 3 .
[0051] In the above technical solution, the residual electrode material with higher volume density and higher strength is added to the composition, and the particle size of the residual electrode material is increased, so as to increase the compressive strength of the prebaked anode without increasing the resistivity or reducing the apparent quality.
[0052] The differences between the calcined coke and the residual electrode material in the embodiments include not only the difference in elemental composition, but also the following differences:
[0053] The coarse coke, medium coke, fine coke, powder coke in the examples and the calcined coke in the comparative examples are prepared by calcining high-sulfur petroleum coke, and their physical and chemical indicators are: true density 2.07g / cm 3 , ash 0.3%, volatile matter 1.07%, sulfur 2.47%, powder resistivity 430μΩ.m, bulk density 0.68g / cm 3 .
[0054] The residual anode material is the residual anode produced by the electrolytic aluminum enterprise. Its physical and chemical indicators are: true density 2.09g / cm 3 , ash 1.47%, volatile matter 1.24%, sulfur 2.45%, powder resistivity 437μΩ.m, bulk density 0.82g / cm 3 ;
[0055] Example 1.
[0056] The specific steps are as follows:
[0057] (1) Obtaining residual electrode material
[0058] The pre-baked anode residues from the aluminum electrolysis are recovered and cleaned and then crushed in two stages. The first stage crushing adopts a deep-cavity jaw crusher, and the second stage crushing adopts a variable frequency impact crusher. The crushed materials are screened with a 12MM screen, and the materials larger than 12MM are returned to the second stage for secondary crushing.
[0059] The crushed materials are screened according to 6-12, 3-6, 1-3, and 0-1mm to ensure that large particles of 6-12mm account for 35wt% and above. If this is not achieved, fine-tune the secondary residual pole crushing frequency or the gap between the impact plates to ensure that large particles of 6-12mm in the residual pole crushing materials account for 35% and above.
[0060] Finally, the contents of each component in the residual electrode material are: large particles (6-12mm) 35wt%, coarse coke (3-6mm) 25wt%, medium coke (1-3mm) 20wt%, and fine powder coke (0-1mm) 20wt%.
[0061] (2) The contents of the components in the prebaked anode composition for aluminum are: 20 wt% coke, 25 wt% medium coke, 10 wt% fine coke, 13 wt% residual anode material, and 32 wt% powder coke.
[0062] The proportion of coarse coke with a particle size of 3-6 mm is greater than 90wt%;
[0063] The proportion of particles with a diameter of 1-3 mm in the medium coke is greater than 85wt%;
[0064] The proportion of fine coke particles with a particle size of 0.075-1 mm is greater than 90wt%;
[0065] The particle size of the coke powder is less than 0.075 mm, accounting for 60±5wt%.
[0066] The specific ingredients are shown in the table below:
[0067] Table 1 Content of each component in the prebaked anode composition for aluminum
[0068]
[0069] Table 2: Composition of residual electrode materials
[0070]
[0071] Example 2.
[0072] The specific operation steps are the same as those in Example 1, except for the differences shown in the table below:
[0073] Table 3 Content of each component in the prebaked anode composition for aluminum
[0074]
[0075] Table 4: Composition of residual electrode materials
[0076]
[0077] Example 3.
[0078] The specific operation steps are the same as those in Example 1, except for the differences shown in the table below:
[0079] Table 5 Content of each component in the prebaked anode composition for aluminum
[0080]
[0081] Table 6: Composition of residual electrode materials
[0082]
[0083] Example 4.
[0084] The specific operation steps are the same as those in Example 1, except for the differences shown in the table below:
[0085] Table 7 Content of each component in the prebaked anode composition for aluminum
[0086]
[0087] Table 8: Composition of residual electrode materials
[0088]
[0089] Example 5.
[0090] The specific operation steps are the same as those in Example 1, except for the differences shown in the table below:
[0091] Table 9 Content of each component in the prebaked anode composition for aluminum
[0092]
[0093] Table 10: Composition of residual electrode materials
[0094]
[0095] Example 6.
[0096] The specific operation steps are the same as those in Example 1, except for the differences shown in the table below:
[0097] Table 11 Content of each component in the prebaked anode composition for aluminum
[0098]
[0099] Table 12: Composition of residual electrode materials
[0100]
[0101] Example 7.
[0102] The specific operation steps are the same as those in Example 1, except for the differences shown in the table below:
[0103] Table 13 Content of each component in the prebaked anode composition for aluminum
[0104]
[0105] Table 14: Composition of residual electrode materials
[0106]
[0107] Example 8.
[0108] The specific operation steps are the same as those in Example 1, except for the differences shown in the table below:
[0109] Table 15 Content of each component in the prebaked anode composition for aluminum
[0110]
[0111] Table 16: Composition of residual electrode materials
[0112]
[0113] Comparative Example 1.
[0114] The specific operation steps are the same as those in Example 1, except for the differences shown in the table below:
[0115] Table 17 Content of each component in the prebaked anode composition for aluminum
[0116]
[0117] Table 18 Composition of calcined coke
[0118]
[0119] Comparative Example 2.
[0120] The specific operation steps are the same as those in Example 1, except for the differences shown in the table below:
[0121] Table 19 Content of each component in the prebaked anode composition for aluminum
[0122]
[0123] Table 20 Composition of calcined coke
[0124]
[0125] Comparative Example 3.
[0126] The specific operation steps are the same as those in Example 1, except for the differences shown in the table below:
[0127] Table 21 Content of each component in the prebaked anode composition for aluminum
[0128]
[0129] Table 22 Composition of calcined coke
[0130]
[0131] Comparative Example 4.
[0132] The specific operation steps are the same as those in Example 1, except for the differences shown in the table below:
[0133] Table 23 Content of each component in the prebaked anode composition for aluminum
[0134]
[0135] Comparative Example 5.
[0136] The specific operation steps are the same as those in Example 1, except for the differences shown in the table below:
[0137] Table 24 Content of each component in the prebaked anode composition for aluminum
[0138]
[0139] Table 25: Composition of residual electrode materials
[0140]
[0141] Comparative Example 6.
[0142] The specific operation steps are the same as those in Example 1, except for the differences shown in the table below:
[0143] Table 26 Content of each component in the prebaked anode composition for aluminum
[0144]
[0145] Table 27: Composition of residual electrode materials
[0146]
[0147]
[0148] The formulations of Examples 1-8 and Comparative Examples 1-6 were prepared into products by a vibration molding process. The specific operation is to weigh the ingredients of the above composition, put them into a high-temperature kneading pot for heating and premixing according to the formulation, add modified liquid asphalt to knead into a plastic paste after the temperature reaches above 130°C, cool it to 140°C, send it into a molding machine mold box for vibration pressure molding, and then send it to a baking furnace to heat it to 1050°C for baking to become a prebaked anode for electrolytic aluminum.
[0149] The performance of the manufactured prebaked anodes was tested. No less than 200 prebaked anodes were sampled for each embodiment and no less than 20 prebaked anodes were sampled for each comparative example. The average values of the test results are shown in Table 28.
[0150] Table 28
[0151]
[0152] Combined with Table 28, the following conclusions can be drawn:
[0153] (1) From Comparative Examples 1-4, it can be seen that increasing the proportion of large particle formula is beneficial to improving the compressive strength of aluminum prebaked anode. However, as the large particle material increases, its resistivity increases, the apparent density decreases, and the appearance deteriorates.
[0154] (2) It can be seen from Examples 2-7 and Example 1 and Comparative Examples 4-6 that when the amount of large particles added to the residual electrode material is less than 5 wt %, the improvement on the compressive strength performance is not obvious.
[0155] (3) By comparing Examples 2-7 with Example 8, it can be seen that when the residual electrode material content in the aluminum prebaked anode formula is too high, although the compressive strength and apparent density will be improved and the resistivity will be reduced, the ash content is too high and the appearance is deteriorated.
[0156] (4) By comparing Examples 2-7 with Comparative Examples 1-4, it can be seen that the formulation of the present invention increases the compressive strength of the prebaked anode for aluminum while improving the apparent density and reducing the resistivity.
[0157] Combining the above embodiments, it can be seen that the technical solution of the present invention solves the problem of difficulty in balancing the apparent density, resistivity and compressive strength, and achieves the effect of improving the compressive strength of the prebaked anode without reducing the apparent density and increasing the resistivity. After the applicant adopted the technical solution of the present invention, the compressive strength of the prebaked anode for aluminum was increased from an average of 36MPa to 41MPa, the compressive strength was not less than 40MPa, the resistivity was reduced from 60.32μΩ·m to below 60μΩ·m, and the volume density was increased from 1.54g / cm 3 Increased to 1.56g / cm 3 .
[0158] The above is only a preferred embodiment of the embodiment of the present invention, and does not impose any form of limitation on the embodiment of the present invention. Any simple modification, equivalent changes and modifications made to the above embodiment based on the technical essence of the embodiment of the present invention are still within the scope of the technical solution of the embodiment of the present invention.
Claims
1. A composition for a prebaked anode for aluminum, characterized in that: include: Coarse coke 18-20wt%, medium coke 25-27wt%, fine coke 7-10wt%, residual electrode material 15-18wt%, and powder coke 32-34wt%; The coarse coke has a particle size of 3-6 mm and accounts for more than 90wt%; The proportion of the particles with a diameter of 1-3 mm in the middle coke is greater than 85wt%; The fine coke has a particle size of 0.075-1 mm, accounting for more than 90wt%; The powdered coke has a particle size of less than 0.075 mm and accounts for more than 60±5wt%; The proportion of the residual electrode material with a particle size of 6-12 mm is not less than 35 wt %; The residual electrode materials include: large particles ≥ 35wt%, coarse coke 25-30wt%, medium coke 15-25wt%, and fine powder coke less than 25wt%; The particle size of the large particles is 6-12 mm; The coarse coke particle size is 3-6 mm; The particle size of the middle coke is 1-3 mm; The particle size of the fine coke powder is 0-1 mm.
2. The composition according to claim 1, characterized in that The content of large particles in the composition is not less than 5wt%.
3. A prebaked anode for aluminum, characterized in that: The composition is prepared by using the composition described in any one of claims 1 to 2.
4. The prebaked anode according to claim 3, characterized in that: The prebaked anode has a compressive strength greater than 40 MPa, a resistivity less than 60 μΩ·m, and a volume density greater than 1.55 g / cm 3 .
Citation Information
Patent Citations
Carbon prebaked anode
CN101974766A
Method for preparing prebaked anode by using aluminum electrolysis waste carbon cathode
CN105441979A